Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

First record of the non-native seagrass Halophila stipulacea (Forsskål) Ascherson in Mallorca (Balearic Islands, Spain): Expanding its Western Mediterranean distribution - ANDRES ARONA; LUCIA LOUBET; GEMA HERNÁN; BALMA ALBALAT; EMMANUELLA ORERO-RUBIO; XESCA REYNÉS; BENJAMI REVIRIEGO; ENRIC BALLESTEROS; FIONA TOMAS (Mediterranean Marine Science, 2026)
Halophila stipulacea is one of the first Lessepsian migrants to colonize the Mediterranean Sea (in 1894) after the opening of the Suez Canal. Since then, it has progressively expanded its distribution westward across the basin. Here, we report for the first time the presence of H. stipulacea in Palma Bay (Mallorca, Balearic Islands, Spain), representing the westernmost known occurrence of the species in the Mediterranean Sea. Initial surveys revealed that H. stipulacea patches (growing on sandy bottoms at ca.16 m depth) were not stable in the colonized area, disappearing in the first reported location (November 2023) and being found innearby areas a few months later (January 2024). Additionally, we collected samples at both sites to assess biomass and morphological traits of H. stipulacea in its early stages of colonization. Morphological data indicate that H. stipulacea in November 2023 exhibited larger leaf areas and longer rhizome internode length, producing smaller shoots in winter, when minimum registered temperatures were 14.5° C. We highlight the need for continued monitoring to assess the spread and possible ecological impacts of H. stipulacea on native species in the recently invaded areas.

An ecosystem-based index for Mediterranean coralligenous reefs: A protocol to assess the quality of a complex key habitat - Patrick Astruch; Charles-François Boudouresque; Mélanie Cabral; Thomas Schohn; Enric Ballesteros; Denise Bellan-Santini; Bruno Belloni; Carlo Nike Bianchi; Olivia Cassetti; Pierre Chevaldonné; Maïa Fourt; Paolo Guidetti; et al. (Marine Pollution Bulletin, 2025)

Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

Correction: Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2025)

Survival of viruses in water microcosms - Inés Girón-Guzmán; Irene Falcó; Enric Cuevas-Ferrando; Sandra Ballesteros; Regino Barranquero; Gloria Sánchez (Science of The Total Environment, 2025)

Assessing the diversity and species composition in macroinvertebrate assemblages thriving in shallow water macroalgal habitats: Structural complexity is not always better - Susana Pinedo; Esther Jordana; Enric Ballesteros (Marine Environmental Research, 2024)

On the presence of an unexpected meadow of Penicillus capitatus Lamarck (Bryopsidales: Chlorophyta) in Mallorca, Balearic Islands, Western Mediterranean - ANDREA HIERRO; ENRIC BALLESTEROS; JULIA MAÑEZ-CRESPO; XESCA REYNÉS; FIONA TOMAS (Mediterranean Marine Science, 2024)
An unexpected meadow of the warm-water alga Penicillus capitatus was found thriving in sandy bottoms between 16 and 21 m depth in Mallorca, Balearic Islands. Plant densities and benthic coverage were very high when compared to most Mediterranean meadows of this species. As it is common in tropical meadows of this species, all the individuals were found in a Penicillus morphological state, whereas most Mediterranean individuals are always found in the filamentous (Espera) state. Due to the high biomass of the populations, the contribution to the primary productivity of the sandy bottoms it colonizes should be far from negligible. If the expansion of these species continues, the annual calcium carbonate production of the Balearic continental shelf will increase and previous estimated budgets will have to be reconsidered. Since no genetic analysis of the specimens have been performed so far, it is still early to know if the studied populations have been originated by native Mediterranean specimens or from a cryptic lineage of Western Atlantic or Macaronesian origin. Whatever the answer is, the current bloom of this population in an environment completely devoid of this species in the recent past, provides new evidence of the current tropicalization of the Mediterranean caused by global warming.

Mass flowering and unprecedented extended pseudovivipary in seagrass (Posidonia oceanica) after a Marine Heat Wave - Fiona Tomas; Gema Hernan; Julia Mañez-Crespo; Andrés Arona; Daniela Haverbeck Meléndez; Xesca Reynés; Jonatan Delgado; Gabriele Procaccini; Enric Ballesteros (Marine Pollution Bulletin, 2024)

Escarpments within Mediterranean seagrass Posidonia oceanica meadows increase habitat heterogeneity and structural complexity enhancing fish diversity and biomass - Enric Gomis; Enric Ballesteros; Irene Bernabeu; Karina Inostroza; Miguel A. Mateo; Oscar Serrano (Frontiers in Marine Science, 2024)
Seagrass meadows provide important ecosystem services including carbon sequestration, coastal protection from erosion, and sustained biodiversity and fisheries thereby improving the wellbeing and livelihoods of coastal communities. The erosion of millenary deposits of intertwined roots and rhizomes of Posidonia results in the formation of three-dimensional structures named escarpments that constitute a biogenic reef habitat. However, the natural history of seagrass escarpments including their formation processes and their role as habitat for reef fauna and flora remains poorly understood. This research located and characterized Posidonia oceanica escarpments in Menorca (Balearic Islands) and compared structural complexity and fish assemblages among seagrass escarpments, seagrass meadows, rocky substrates and bare sand with emphasis on its role as habitat and shelter for typical rocky fish. Fish abundance and biomass were similar between seagrass escarpments and rocky substrates (P > 0.05), but significantly lower in seagrass meadows (P < 0.001). The large number of caves found along seagrass escarpments provide shelter to fish, including species only associated to rocky substrates. Seagrass meadows form a rather homogenous habitat within their canopy, but the presence of seagrass escarpments enhances habitat heterogeneity and structural complexity along with fish abundance and biomass at the seascape level. This study enhances understanding on the ecological importance of seagrass escarpments.

An Atlantic origin for the introduced species Halimeda incrassata (Bryopsidales, Chlorophyta) - HEROEN VERBRUGGEN; ENRIC BALLESTEROS (Mediterranean Marine Science, 2024)
Not applicable. This is a comment on a recently published study.

Functional changes across marine habitats due to ocean acidification - Núria Teixidó; Jérémy Carlot; Samir Alliouane; Enric Ballesteros; Cinzia De Vittor; Maria Cristina Gambi; Jean‐Pierre Gattuso; Kristy Kroeker; Fiorenza Micheli; Alice Mirasole; Valeriano Parravacini; Sébastien Villéger (Global Change Biology, 2024)
Global environmental change drives diversity loss and shifts in community structure. A key challenge is to better understand the impacts on ecosystem function and to connect species and trait diversity of assemblages with ecosystem properties that are in turn linked to ecosystem functioning. Here we quantify shifts in species composition and trait diversity associated with ocean acidification (OA) by using field measurements at marine CO 2 vent systems spanning four reef habitats across different depths in a temperate coastal ecosystem. We find that both species and trait diversity decreased, and that ecosystem properties (understood as the interplay between species, traits, and ecosystem function) shifted with acidification. Furthermore, shifts in trait categories such as autotrophs, filter feeders, herbivores, and habitat‐forming species were habitat‐specific, indicating that OA may produce divergent responses across habitats and depths. Combined, these findings reveal the importance of connecting species and trait diversity of marine benthic habitats with key ecosystem properties to anticipate the impacts of global environmental change. Our results also generate new insights on the predicted general and habitat‐specific ecological consequences of OA.

Tissue nutrient contents of the red alga Ellisolandia elongata as a tool to assess the ecological status in NW Mediterranean coastal waters - Pinedo Susana; Esther Jordana; Enric Ballesteros (Estuarine, Coastal and Shelf Science, 2023)

A decision-support framework for the restoration of Cystoseira sensu lato forests - Christopher J. Smith; Jana Verdura; Nadia Papadopoulou; Simonetta Fraschetti; Emma Cebrian; Erika Fabbrizzi; Margalida Monserrat; Matilde Drake; Silvia Bianchelli; Roberto Danovaro; Dania Abdul Malak; Enric Ballesteros; et al. (Frontiers in Marine Science, 2023)
Macroalgal forests characterised by species of the genus Cystoseira sensu lato form important shallow coastal rocky habitats in the Mediterranean Sea. These forests support a high biodiversity and provide important ecosystem services and societal benefits. Currently these habitats are often in a poor condition in many areas, due to loss and degradation from both anthropogenic and climate stressors. Restoration has recently moved to the forefront of the United Nations and European Union agendas to reverse this trend, particularly in the last decade with the implementation of various international policies. However, this has been in the form of generic targets (e.g., restoration of 30% of degraded habitats by 2030) and has not been linked to specifically what habitat or species to restore, where and how. Initial targets have been missed, new targets are expected through the proposed EU Nature Restoration Law, but overall guidance is still lacking. There are few specific guides to marine habitat restoration limited to mostly seagrass, corals and shellfish. As a priority action for the recovery of coastal marine ecosystems a decision-support framework has been developed for the restoration of Mediterranean macroalgal forests, comprising a stepwise decision tree with additional descriptions of key elements to be considered for a restoration action. The decision tree includes steps concerning current and historical forest presence, site local condition assessment and choice of actions. Key considerations include restoration implementation (competence, society and support, finance and governance), success evaluation (at the target species and the ecosystem level) and long-term management. The framework builds on existing work on Cystoseira s.l. restoration, the work carried out in the EU AFRIMED project, but also on principles and guidelines in place for both generic and specific marine habitats. The work reported here has involved the expertise of scientists and information from stakeholders. Gaps were identified and recommendations were made, dealing with stressors, coordinating and networking stakeholders, integrating top down policy and bottom up initiatives, funding of restoration actions, establishing synergies between restoration, conservation and marine spatial planning and finally communication and publicity.

Addressing marine restoration success: evidence of species and functional diversity recovery in a ten-year restored macroalgal forest - Cristina Galobart; Enric Ballesteros; Raül Golo; Emma Cebrian (Frontiers in Marine Science, 2023)
Active restoration actions are becoming increasingly common for the recovery of degraded ecosystems. However, establishing when an ecosystem is fully restored is rarely achieved, since the recovery of entire communities needs long-term trajectories. The lack of evidence of success is even more severe in marine ecosystems, especially in the context of macroalgal forests, where beyond the vegetation structure and species diversity there is no approximation determining the recovery of the overall functionality. Trait-based ecology facilitates the link between species composition and ecosystem functions and processes. In this study, we used a trait-based approach to assess functional recovery ten years after the start of a restoration action in a marine macroalgal forest. Species and functional diversity were compared among the restored locality, a nearby locality where the expansion of the restoration is naturally occurring, a neighbouring non-restored locality (at a distance of a few meters), and the only two remaining localities dominated by the same structural macroalga that were used as reference (non-perturbed). Species diversity and composition of the restored locality were similar to those found in reference macroalgal forests, while the non-restored and expansion locality showed different species composition and lower species diversity. Functional richness was 4-fold higher in the restored locality than in the non-restored one, even surpassing one reference macroalgal locality. The restored locality showed a greater number of trait categories, especially traits related to higher structural complexity and longer life spans, indicating changes in ecosystem functions and processes. The restoration of a canopy-forming macroalga is the first step to achieving the recovery of an entire macroalgal forest (i.e., associated species and functional diversity). The application of traditional taxonomical indices plus functional parameters provides useful insights into the assessment of the success of restoration actions at the community level, emerging as a promising approach to be replicated and contrasted in other marine and terrestrial ecosystems.

Elemental cycles in the coralline alga Neogoniolithon hauckii as a recorder of temperature variability in the Mediterranean Sea - Steffen Hetzinger; Madleen Grohganz; Jochen Halfar; Ed Hathorne; Enric Ballesteros; Diego K. Kersting (Frontiers in Marine Science, 2023)
Coralline algae play important ecological roles throughout the photic zone of the world’s oceans. Recent studies have shown that attached-living coralline algae can contain records of past climate variability. So far, algal-based paleo-reconstructions are mainly available from mid- to high-latitudes, while in low latitude and temperate regions only few examples exist. Here, we investigate samples from the attached-living encrusting coralline algal species Neogoniolithon hauckii (Rothpletz) R.A Townsend & Huisman [= Neogoniolithon mamillosum (Hauck) Setchell & L.R. Mason, nom illeg.] from a temperate site in the Mediterranean Sea to assess its potential as an environmental recorder. The specimens were collected at different water depths (20 and 40 m) in the Columbretes Islands (Spain). Sclerochronological analysis of sectioned samples revealed seasonal growth patterns. Mg/Ca, Li/Ca, and Ba/Ca ratios were measured in the algal skeletons using laser ablation inductively coupled mass spectrometry (LA-ICP-MS) in ultra-high resolution. We report a mean vertical extension rate of 1.1 to 1.2 mm/year (based on analysis of Mg/Ca cycles in 40 m and 20 m samples), representing the first growth rate measurement for this species. In addition, subannual banding patterns were mapped, measured, and could be linked to high frequency variability in laser-analyzed Mg/Ca ratios. Elemental ratios analyzed in Neogoniolithon hauckii were compared to in situ water temperatures measured at the water depth of sample collection. Our results show significant positive relationships between algal Mg/Ca (R=0.55) as well as Li/Ca ratios (R=0.46) and in situ measured temperature data (40 m specimen). Ba/Ca ratios show no significant correlation to temperature and may be influenced by other factors. These data suggest potential of this species for climate reconstructions in warm-temperate regions as Neogoniolithon hauckii is not only widely distributed in the Mediterranean, but also one of the few species that may be used as a temperature archive for mesophotic coralligenous assemblages that are strongly affected by the recent anthropogenic temperature rise. Further calibration studies are needed to test the element-temperature relationships on samples with longer growth records and in different settings and water depths.

Metabarcoding the eukaryotic community of a threatened, iconic Mediterranean habitat: Posidonia oceanica seagrass meadows - Xavier Turon; Jesús Zarcero; Adrià Antich; Owen Simon Wangensteen; Enric Ballesteros; Emma Cebrian; Candela Marco-Méndez; Teresa Alcoverro (Frontiers in Marine Science, 2023)
Against the accelerating pace of worldwide species extinction, reliable biodiversity assessments are critical, both as baselines and to track potential declines. DNA metabarcoding techniques allow for fast and comprehensive assessment of biodiversity in both terrestrial and marine habitats. However, these methods need to be adapted and standardised for each ecosystem in order to be effective. Seagrass meadows are among the most diverse marine habitats and are irreplaceable in terms of the ecosystem services they provide, yet metabarcoding has never been implemented for these systems. In this study, we developed and tested a protocol for metabarcoding the eukaryotic community of meadows of the iconic species, Posidonia oceanica L. (Delile). This seagrass is the main habitat-forming species in Mediterranean coastal waters and is known for its high diversity due to the structural complexity of its canopy and rhizome structures. This habitat is experiencing a range-wide retreat, and there is an urgent need for fast and efficient methods for its biomonitoring and detection of early changes. Our proposed method involves direct sampling of the community, collecting and processing the leaves and rhizome strata separately. To test the utility of the method in distinguishing between different meadow conditions, we sampled two distinct meadows that differ in their prevailing wind and surge conditions, and a nearby rocky reef for comparison. We then adapted a method and pipeline for COI metabarcoding using generalist primers that target the eukaryote diversity present. We detected a high diversity in the two meadows analysed (3,350 molecular operational taxonomic units, dominated by Metazoa and Archaeplastida) and a clear differentiation of the seagrass samples from those of the nearby rocky reefs. The leaves and rhizomes harboured clearly distinct assemblages, and differences were also detected between the two meadows sampled. This new tool has the potential to deliver big biodiversity data for seagrass habitats in a fast and efficient way, which is crucial for the implementation of protection and management measures for this key coastal habitat.

Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2023)
Introduction Coastal detrital bottoms (CDB) are one of the most extensive habitats of the continental shelf worldwide, in the upper levels of the circalittoral zone. Hosting a diverse community structured by sediment grain size, trophic interactions and calcified organisms, CDB exhibit important ecological functions. In the Mediterranean Sea, CDB are constituted by recent elements partly provided by adjacent infralittoral and circalittoral ecosystems. Since the 2010s, the offshore extension of many Marine Protected Areas (MPAs) has resulted in the incorporation of vast areas of CDB, raising the issue of their management. The Marine Strategy Framework Directive (MSFD) has embraced the concept of an ecosystem-based approach involving taking into account the functioning of marine habitats and their related ecosystem services. The purpose of this paper is to propose an ecosystem-based quality index (EBQI) tested on CDB from the north-western Mediterranean Sea, focusing mainly on epibenthic assemblages. Methods The first step has been to define a conceptual model of the CDB functioning, including the main trophic compartments and their relative weighting, then to identify appropriate assessment methods and potential descriptors. Twenty-nine sites were sampled along the coast of Provence and French Riviera (Southern France). Study sites were chosen with a view to encompassing a wide range of hydrological conditions and human pressures. Results Very well-preserved sites were found in Provence in areas without trawling and terrigenous inputs, while impacted and low-ES sites were located in the vicinity of urbanized areas. The cover of rhodoliths characterizes the seascape and might be an indicator of the good ES of CDB and reduced human pressure. However, the absence of rhodoliths may also be induced by natural phenomena. Discussion The EBQI designed for CDB proved representative and useful for a functional assessment based on epibenthic assemblages. However, some descriptors have shown their limitations and should be further explored. We highlight here the priority of establishing an index corresponding to a societal demand (e.g., European Directives, Barcelona convention) as a basis for a broad and large-scale assessment, for practical reasons. We stress the need to better apprehend the role of the macro-infauna and to extend this index over a wider geographical scale.

Assessing the expansion and success of a restored population of Gongolaria barbata (Stackhouse) Kuntze (Fucales, Phaeophyceae) using high-precision positioning tools and size distribution frequencies - ALICIA GRAN; JUANCHO MOVILLA; ENRIC BALLESTEROS; MARTA SALES; IGNACIO BOLADO; CRISTINA GALOBART; MARIA ELENA CEFALÌ (Mediterranean Marine Science, 2022)
Ongoing human pressures over recent decades have caused the loss and ensuing impoverishment of the complexity and diversity of Mediterranean habitats dominated by algal species of the order Fucales. Gongolaria barbata, a habitat-forming Fucales species that has disappeared in several places across the Mediterranean, was reintroduced in a cove (Cala Teulera, Maó Bay, Menorca) where it was known to have been locally extinct for more than 40 years. Reintroduction was performed in 2011 using innovative non-destructive techniques. Here we describe the expansion patterns of the population ten years after its reintroduction, and we look at the size-structure distribution of the restored population compared to one of the only natural populations known in Spain (Fornells Bay, Menorca). Newly settled individuals exhibit a progressive dispersal pattern from restoration sites, favouring rocky substrates at the shallowest level parallel to the shore. The area occupied by G. barbata has increased by almost three orders of magnitude in ten years, from approximately 3.6 m2 of the initially restored area to a current restored area of 2093 m2. Recruits and juveniles dominate the restored population but some individuals have reached large size classes, the overall size distribution resembling the reference population. The high-resolution cartography included in our study enables an accurate mid to long-term assessment of the expansion of G. barbata. Incorporating such tools in restored marine forests would facilitate the implementation of efficient management policies that will help reinforce their conservation

Learning takes time: Biotic resistance by native herbivores increases through the invasion process - Jorge Santamaría; Raül Golo; Jana Verdura; Fiona Tomas; Enric Ballesteros; Teresa Alcoverro; Rohan Arthur; Emma Cebrian (Ecology Letters, 2022)
As invasive species spread, the ability of local communities to resist invasion depends on the strength of biotic interactions. Evolutionarily unused to the invader, native predators or herbivores may be initially wary of consuming newcomers, allowing them to proliferate. However, these relationships may be highly dynamic, and novel consumer–resource interactions could form as familiarity grows. Here, we explore the development of effective biotic resistance towards a highly invasive alga using multiple space‐for‐time approaches. We show that the principal native Mediterranean herbivore learns to consume the invader within less than a decade. At recently invaded sites, the herbivore actively avoided the alga, shifting to distinct preference and high consumptions at older sites. This rapid strengthening of the interaction contributed to the eventual collapse of the alga after an initial dominance. Therefore, our results stress the importance of conserving key native populations to allow communities to develop effective resistance mechanisms against invaders.

Species characterization of soft bottom habitats by depth and sediment particle size on the Catalan coast (NW Mediterranean): unexpected species composition of the assemblages - SUSANA PINEDO; ESTHER JORDANA; ENRIC BALLESTEROS (Mediterranean Marine Science, 2022)
The aim of the study is to describe the macrofaunal composition of marine soft bottom habitats on the Catalan coast between a depth of 3 and 35 meters, considering all groups of macroinvertebrates. The study also aims to compare our data with previous studies focused on the NW Mediterranean and to define the variables that drive assemblage composition. Depending on the species composition and the structure of the assemblages, six different habitats, mainly defined by depth and sediment granulometry, are described. Shallow ( 20 m) habitats are easily distinguished and are subdivided in three habitats each: (1) very coarse and coarse sediments (coarse sediments); (2) medium, fine and very fine sands (fine sediments); and (3) muddy sediments. Fine sediments in both shallow and deep waters have emerged as the most common and extensive habitats along the coast up to a depth of 35 meters. Neither coarse nor muddy habitats are frequent. The characterization of shallow habitats produced some unexpected results with respect to previous studies: Spisula subtruncata and Lucinella divaricata were dominant, while neither Ditrupa arietina nor Owenia fusiformis, previously mentioned as dominant polychaetes in shallow fine sand habitats, were common. Polychaetes were, in general, the dominant group (both in species richness and abundance) in the six habitats, except in shallow fine sediments, which were dominated by mollusks. The study is a benchmark for future monitoring of soft bottom habitats on the Catalan coast to a depth of 35 meters.

Spatial and temporal patterns in the coral assemblage at Clipperton Atoll: a sentinel reef in the Eastern Tropical Pacific - J. J. Adolfo Tortolero-Langarica; Eric Clua; Fabián A. Rodríguez-Zaragoza; Jennifer E. Caselle; Alma P. Rodríguez-Troncoso; Mehdi Adjeroud; Alan M. Friedlander; Amílcar L. Cupul-Magaña; Enric Ballesteros; Juan P. Carricart-Ganivet; Eric K. Brown (Coral Reefs, 2022)

On the edge: segregation and coexistence between epibenthic fish species in Mediterranean mesophotic habitats - Diego K. Kersting; Luisa Mangialajo; Enric Ballesteros (Marine Biology, 2021)

Is the local extinction of Pinna nobilis facilitating Pinna rudis recruitment? - DIEGO KURT KERSTING; ENRIC BALLESTEROS (Mediterranean Marine Science, 2021)
Until the late 2010s the spiny fan-mussel Pinna rudis shared habitat in many Mediterranean sites with Mediterranean endemic Pinna nobilis, which dominated in abundance but that has gone locally extinct in most of its distribution area due to a recent widespread disease outbreak. In the Columbretes Islands Marine Reserve (NW Mediterranean) both species coexisted until 2017, when P. nobilis populations completely disappeared. In spring 2021 we revisited 7 permanent plots covering 1,485 m2 that had been previously monitored during the period from 2005 to 2009. We found that although previous studies described P. rudis populations as stable with low recruitment rates, recruitment after 2017 increased in comparison to 2005-2009. At least two cohorts of recruits (~3 and ~1 year in age) were to be found both within the plots as well as in other areas throughout the Columbretes archipelago, colonizing areas previously occupied by P. nobilis. We hypothesize that P. rudis has been benefited by the local extinction of the sibling species P. nobilis, most probably as a result of reduced interspecific competition. The ecological role once played mainly by P. nobilis as the dominant species, might now be taken over by P. rudis, whose populations could grow during the oncoming years.

The role of competition and herbivory in biotic resistance against invaders: a synergistic effect - Jorge Santamaría; Fiona Tomas; Enric Ballesteros; Juan M. Ruiz; Jaime Bernardeau‐Esteller; Jorge Terrados; Emma Cebrian (Ecology, 2021)
Invasive species pose a major threat to global diversity, and once they are well established their eradication typically becomes unfeasible. However, certain natural mechanisms can increase the resistance of native communities to invaders and can be used to guide effective management policies. Both competition and herbivory have been identified as potential biotic resistance mechanisms that can limit plant invasiveness, but it is still under debate to what extent they might be effective against well‐established invaders. Surprisingly, whereas biotic mechanisms are known to interact strongly, most studies to date have examined single biotic mechanisms separately, which likely influences our understanding of the strength and effectiveness of biotic resistance against invaders. Here we use long‐term field data, benthic assemblage sampling, and exclusion experiments to assess the effect of native assemblage complexity and herbivory on the invasion dynamics of a successful invasive species, the alga Caulerpa cylindracea . A higher complexity of the native algal assemblage limited C. cylindracea invasion, probably through competition by canopy‐forming and erect algae. Additionally, high herbivory pressure by the fish Sarpa salpa reduced C. cylindracea abundance by more than four times. However, long‐term data of the invasion reflects that biotic resistance strength can vary across the invasion process and it is only where high assemblage complexity is concomitant with high herbivory pressure, that the most significant limitation is observed (synergistic effect). Overall, the findings reported in this study highlight that neglecting the interactions between biotic mechanisms during invasive processes and restricting the studied time scales may lead to underestimations of the true capacity of native assemblages to develop resistance to invaders.

Herbivory on the Invasive Alga Caulerpa cylindracea: The Role of Omnivorous Fishes - Jorge Santamaría; Fiona Tomas; Enric Ballesteros; Emma Cebrian (Frontiers in Marine Science, 2021)
Herbivory has long been considered an important component of biotic resistance against macroalgae invasions in marine habitats. However, most of the studies on herbivory of invasive algae refer only to consumption by strictly herbivorous organisms, whereas consumption by omnivorous species has been largely ignored and rarely quantified. In this study, we assess whether the commonest omnivorous sparid species in the Mediterranean Sea are consuming the highly invasive alga, Caulerpa cylindracea , and determine both, its importance in their diet and their electivity toward it as a source of food. Our results confirm that three of the four fish species studied regularly consume C. cylindracea , but in most cases, the importance of C. cylindracea in the diet is low. Indeed, the low electivity values indicate that all species avoid feeding on the invasive alga and that it is probably consumed accidentally. However, despite animals and detritus being the main food for these sparid species, several individual specimens were found to have consumed high amounts of C. cylindracea . This suggests a potential role that these fish species, being really abundant in shallow rocky bottoms, may play in controlling, to some extent, the abundance of the invader.

Photosynthetic performances of two deep‐water canopy‐forming fucoid algae across a depth gradient: Interspecific variability and short‐term adaptation to the light environment - Natàlia Sant; Enric Ballesteros (Marine Ecology, 2021)
Deep‐water canopy‐forming algae Gongolaria montagnei var. compressa and Ericaria zosteroides (Fucales: Ochrophyta) co‐exist in mixed populations, the first taxa dominating at the upper limit of distribution (20 m) and the second at the lower limit (40 m). This depth distribution pattern is consistent with the photosynthetic performances of both taxa, with E. zosteroides showing higher photosynthetic efficiency (α) and lower light at saturation ( I k ) and compensation ( I c ) than G. montagnei var. compressa . Neither photosynthesis at saturation ( P max ) nor dark respiration showed any significant change at the species level. G. montagnei v. compressa showed higher P max and α at 20 and 40 m, but E. zosteroides did not follow the same trend, although both I k and I c decreased with depth in this species, pointing to an increased capacity of E. zosteroides to show photo‐adaptation. Each species maintained its P sat values when transplanted from the depth where it was dominant to the depth where it was secondary, but in the case of G. montagnei var. compressa it decreased its P sat when transplanted from 40 to 20 m and in the case of E. zosteroides it increased its P sat when transplanted from 20 to 40 m. These results point to a better photosynthetic performance of E. zosteroides than G. montagnei var. compressa at low‐light conditions, information that can be used to improve success in restoration action plans.

Co-occurrence of a reef-building coral and canopy-forming macroalgae in the Mediterranean Sea - ALÈSSIA PONS-FITA; DIEGO K. KERSTING; ENRIC BALLESTEROS (Mediterranean Marine Science, 2021)
Canopy-forming macroalgae are amongst the main competitors of corals by affecting coral recruitment, growth of recruits and adults, fecundity and in the worst-case scenario causing coral bleaching and necrosis. However, potentially reef-building coral Cladocora caespitosa (Linnaeus, 1767) and canopy-forming macroalgae of the order Fucales (Cystoseira sensu lato) are known to concur in a few places of the Mediterranean Sea. Here we look at the small-scale relationships between Cladocora abundance and Cystoseira s. l. densities at three different places where they coexist. Relationships have turned out to be both species and site-specific even though most relationships are neutral, pointing to a predominant concurrence of corals and macroalgae at the small scale. These findings shed new information on the relationship between corals and fleshy macroalgae in a temperate environment and serve as a starting point for future studies addressing the interactions between C. caespitosa and Cystoseira s. l.

Depth distribution of canopy‐forming algae of the order Fucales is related to their photosynthetic features - Natàlia Sant; Enric Ballesteros (Marine Ecology, 2021)
Photosynthetic features and dark respiration of different species of dominant canopy‐forming algae of the Order Fucales (Phaeophyceae) consistently change with depth. Photosynthetic efficiency (α) and light at compensation ( I c ) change according to the amount of light available at each depth, α increasing and I c decreasing with depth. However, the values of light at saturation ( I k ) do not show any depth pattern. Deep‐water species show higher photosynthesis at saturation ( P max ) and lower dark respiration ( R d ) than shallow water ones. This result contrasts with the expected reduction of P max in low light environments shown by terrestrial plants but is consistent with other studies performed in macroalgae, suggesting that P max and α show the same trend of variation in the marine environment. The positive correlation between P max and α cannot be explained by differences in thickness as all tested species show an extremely high morphological similarity. The increase in P max with depth is also coupled to an increase of N and P content in branches, which points to nutrient‐limited photosynthesis in shallow water species.

Modeling Macroalgal Forest Distribution at Mediterranean Scale: Present Status, Drivers of Changes and Insights for Conservation and Management - Erika Fabbrizzi; Michele Scardi; Enric Ballesteros; Lisandro Benedetti-Cecchi; Emma Cebrian; Giulia Ceccherelli; Francesco De Leo; Alan Deidun; Giuseppe Guarnieri; Annalisa Falace; Silvia Fraissinet; Chiara Giommi; et al. (Frontiers in Marine Science, 2020)

Spawning behavior of the tiger grouper (Mycteroperca tigris) in a Caribbean atoll - Richard M. Starr; Enric Ballesteros; Enric Sala; Josep Maria Llenas (Environmental Biology of Fishes, 2018)

The zooxanthellate scleractinian coral Oulastrea crispata (Lamarck, 1816), an overlooked newcomer in the Mediterranean Sea? - SIMONE MARIANI; OSCAR OCAÑA VICENTE; PAULA LÓPEZ-SENDINO; MARÍA GARCÍA; AURORA MARTÍNEZ RICART; JOAQUIM GARRABOU; ENRIC BALLESTEROS (Mediterranean Marine Science, 2018)
The zooxanthellate scleractinian coral Oulastrea crispata, a widely distributed species across central Indo-Pacific nearshore marine habitats, has been first reported from the Mediterranean Sea (Corsica) in 2014. Here we report on two new sites for this species in the NW Mediterranean Sea and provide a general description of external morphological characters of the colonies and a detailed account of the cnidom to help future identifications. Living specimens may appear virtually identical to small colonies (~5 cm) of the Mediterranean zooxanthellate scleractinian Cladocora caespitosa. While this species shows long, ramified, independent corallites, with cylindrical calices, O. crispata has enlarged, cup-like calices, which can be joined by the coenosteum. It also shows clear differences among several groups of nematocysts, principally the presence in the filaments of large penicilli (p-mastigophore) of one type, which are absent in C. caespitosa. Identifications based on underwater observations or even the analysis of photographs may easily lead to misleading identifications. We hypothesize that O. crispata may have gone unnoticed because of misidentifications as C. caespitosa. More detailed research is needed to get reliable maps of the actual distribution of this apparently non-indigenous species in the Mediterranean Sea.

Biodiversity influences invasion success of a facultative epiphytic seaweed in a marine forest - Emma Cebrian; Fiona Tomas; Paula López-Sendino; Montserrat Vilà; Enric Ballesteros (Biological Invasions, 2018)

First record of the gastropod Philinopsis wildpretii (Ortea, Bacallado and Moro, 2003) (Cephalaspidea, Aglajidae) in the Iberian Peninsula - Manuel Ballesteros; Enric Madrenas; Miquel Pontes (Marine Biodiversity, 2018)

Recovery of submersed vegetation in a high mountain oligotrophic soft-water lake over two decades after impoundment - Joan Lluís Riera; Enric Ballesteros; Cristina Pulido; Eglantine Chappuis; Esperança Gacia (Hydrobiologia, 2017)

Seagrass Meadows Provide 3D Habitat for Reef Fish - Oscar Serrano; Eduard Serrano; Karina Inostroza; Paul S. Lavery; Miguel A. Mateo; Enric Ballesteros (Frontiers in Marine Science, 2017)

Location and Associated Carbon Storage of Erosional Escarpments of Seagrass Posidonia Mats - Oscar Serrano; Paul S. Lavery; Lourdes López-Merino; Enric Ballesteros; Miguel A. Mateo (Frontiers in Marine Science, 2016)

Population structure and conservation status of the red gorgonian Paramuricea clavata (Risso, 1826) in the Eastern Adriatic Sea - Silvija Kipson; Cristina Linares; Hrvoje Čižmek; Emma Cebrián; Enric Ballesteros; Tatjana Bakran‐Petricioli; Joaquim Garrabou (Marine Ecology, 2015)
Gorgonians are important structuring species of the Mediterranean hard‐bottom communities that are threatened by disturbances such as increasing seawater temperature, mucilaginous events and destructive fishing, among others. In this study we assessed for the first time the population structure and conservation status of one of the most common gorgonians in the Eastern Adriatic Sea, the red gorgonian Paramuricea clavata . During late spring 2009, nine populations dwelling between 30 and 50 m depth were examined by SCUBA diving along 200 km of the Croatian coastline. The density ranged between 7 and 20 colonies·m −2 . The mean and maximum colony heights were 31.2 ± 22.7 cm (± SD ) and 138 cm, respectively. Two main patterns of P. clavata size frequency distributions were observed: the first one with a higher proportion of juveniles (~30%) observed mostly in the northernmost populations, and the second one with a higher proportion of larger colonies (>25% of colonies >40 cm in height). Regarding the disturbance impact level, the proportion of healthy colonies (with 60%) and the mean extent of injury ( i.e . denuded axis or epibiosis) was 9.7 ± 4% (± SD ), indicating low impacts. Contrasting population size structures with high recruitment in mature populations provides new insights into the demographic structure of the Mediterranean gorgonian forests dwelling in their upper bathymetric range (

Deleterious interaction of light impairment and organic matter enrichment on Isoetes lacustris (Lycopodiophyta, Isoetales) - Eglantine Chappuis; Ana Lumbreras; Enric Ballesteros; Esperança Gacia (Hydrobiologia, 2015)

A critical analysis on the response of macroinvertebrate communities along disturbance gradients: description of MEDOCC (MEDiterranean OCCidental) index - Susana Pinedo; Esther Jordana; Enric Ballesteros (Marine Ecology, 2015)
Macroinvertebrate communities inhabiting shallow sandy bottoms from C atalonia and B alearic I slands coastal waters ( W estern M editerranean) were used to develop the Mediterranean Occidental ( MEDOCC ) index, a new methodology to assess the ecological status ( ES ) according to Water Framework Directive ( WFD ) requirements. The dominance pattern of four ecological groups ( EG ; sensitive, indifferent, tolerant and opportunistic organisms) was studied along a disturbance gradient. Sensitive taxa were present in disturbed situations and tolerant species were related to opportunistic taxa. The thresholds between ES were scaled according to the shifts in the dominance pattern of the EG s. The distribution of the EG s along the gradient of disturbance may vary depending on the studied communities, thus influencing the boundaries defining the ES . With the development of the MEDOCC index it is shown that analysing the response of the communities to the increasing gradient of disturbance is critical to enable an accurate proposal for boundary setting to be made, and to improve the applicability of the indices. AMBI ( AZTI M arine B iotic I ndex), B entix ( B iotic I ndex), and MEDOCC indices were applied to the dataset to compare the ES obtained.

Macrobenthic assemblages, sediment characteristics and heavy metal concentrations in soft-bottom Ebre Delta bays (NW Mediterranean) - Esther Jordana; Susana Pinedo; Enric Ballesteros (Environmental Monitoring and Assessment, 2015)

Relationships Between Heavy Metals Contamination in Shallow Marine Sediments with Industrial and Urban Development in Catalonia (Northwestern Mediterranean Sea) - Susana Pinedo; Esther Jordana; Maria Monia Flagella; Enric Ballesteros (Water, Air, & Soil Pollution, 2014)

Invasive macrophytes in a marine reserve (Columbretes Islands, NW Mediterranean): spread dynamics and interactions with the endemic scleractinian coral Cladocora caespitosa - Diego K. Kersting; Enric Ballesteros; Sònia De Caralt; Cristina Linares (Biological Invasions, 2013)

Biogeographical patterns of algal communities in the Mediterranean Sea: Cystoseira crinita ‐dominated assemblages as a case study - Marta Sales; Enric Ballesteros; Marti J. Anderson; Ljiljana Iveša; Eva Cardona (Journal of Biogeography, 2012)
Aim The aim of this study was to describe the composition, community structure and biogeographical variation of subtidal algal assemblages dominated by the brown alga Cystoseira crinita across the Mediterranean Sea. Location The Mediterranean coast, from Spain (1°25′ E) to Turkey (30°26′ E). Methods Data on the species composition and structure of assemblages dominated by the species C. crinita were collected from 101 sites in nine regions across the Mediterranean Sea. Multivariate and univariate statistical tools were used to investigate patterns of variation in the composition of the assemblages among sites and regions, and to compare these with previously defined biogeographical regions. Linear regressions of species richness versus longitude and versus latitude were also carried out to test previously formulated hypotheses of biodiversity gradients in the Mediterranean Sea. Results The main features characterizing C. crinita ‐dominated assemblages across the Mediterranean included a similar total cover of species, a similar cover of C. crinita , and consistency in the presence of the epiphyte Haliptilon virgatum . Biogeographical variation was detected as shifts in relative abundances of species among regions, partly coinciding with previously described biogeographical sectors. A significant positive correlation was found between species richness and latitude, while no significant correlation was detected between species richness and longitude. Main conclusions The patterns of variation in community structure detected among the studied regions reflected their geographical positions quite well. However, latitude seemed to contribute more to the explanation of biological patterns of diversity than did geographical distances or boundaries, which classically have been used to delimit biogeographical sectors. Moreover, the positive correlation between species richness and latitude reinforced the idea that latitude, and possibly temperature as a related environmental factor, plays a primary role in structuring biogeographical patterns in the Mediterranean Sea. The lack of correlation between species richness and longitude contradicts the notion that there is a decrease in species richness from west to east in the Mediterranean, following the direction of species colonization from the Atlantic.

Do native herbivores provide resistance to Mediterranean marine bioinvasions? A seaweed example - Emma Cebrian; Enric Ballesteros; Cristina Linares; Fiona Tomas (Biological Invasions, 2011)